KCC2 knockdown impairs glycinergic synapse maturation in cultured spinal cord neurons - Schwale, Chrysovalandis; Schumacher, Stefanie; Bruehl, Claus; Titz, Stefan; Schlicksupp, Andrea; Kokocinska, Mirka; Kirsch, Joachim; Draguhn, Andreas; Kuhse, Jochen (Histochemistry and cell biology, 2016)
Synaptic inhibition in the spinal cord is mediated mainly by strychnine-sensitive glycine (GlyRs) and by γ-aminobutyric acid type A receptors (GABAAR). During neuronal maturation, neonatal GlyRs containing α2 subunits are replaced by adult-type GlyRs harboring α1 and α3 subunits. At the same time period of postnatal development, the transmembrane chloride gradient is changed due to increased expression of the potassium-chloride cotransporter (KCC2), thereby shifting the GABA- and glycine-mediated synaptic currents from mostly excitatory depolarization to inhibitory hyperpolarization. Here, we used RNA interference to suppress KCC2 expression during in vitro maturation of spinal cord neurons.